2018
DOI: 10.1111/ner.12689
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Risk Factors of Unplanned 30-Day Readmission Following Spinal Cord Stimulator Implantation

Abstract: Our study suggests that infectious and mechanical complications are the primary drivers of unplanned 30-day readmission after SCS implantation, with obesity as an independent predictor of unplanned readmission. Given the technological advancements in SCS, repeated studies are necessary to identify factors associated with unplanned 30-day readmission rates after SCS implantation to improve patient outcomes and reduce associated costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…SSIs are associated with significant humanistic, economic, and clinical consequences. Recent publications have highlighted the consequences of SSIs for implantable pain therapies and the low levels of compliance with evidence‐based guidelines . An analysis of the United States Closed Claims Project data base on implantable pain therapies indicated that infection was the most common damaging event (i.e., 23% of all claims) for surgical device‐related claims .…”
Section: Introductionmentioning
confidence: 99%
“…SSIs are associated with significant humanistic, economic, and clinical consequences. Recent publications have highlighted the consequences of SSIs for implantable pain therapies and the low levels of compliance with evidence‐based guidelines . An analysis of the United States Closed Claims Project data base on implantable pain therapies indicated that infection was the most common damaging event (i.e., 23% of all claims) for surgical device‐related claims .…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the United States Closed Claim Project database showed that the most common complication for surgical device-related claims for implantable pain therapies was infection, accounting for 23% of all claims 15. According to a research analysis looking at insurance claims database, the infection rate for SCS was found to be 3.11% 16. Provenzano et al studied infection rates and annual expenditures related to infections following SCS implantation and implantable pulse generators (IPG) replacement.…”
Section: Resultsmentioning
confidence: 99%
“…Although the number of patients with obesity having SCS implants have increased over the years the cost of hospitalization was not different when compared with non-obese individuals undergoing SCS implant 69. Other observational studies have observed obesity to be an independent predictor of 30-day readmission after SCS implantation,70 as well as higher risk of complications including mechanical complications and lead migration 71. A significant negative association of body mass index (BMI) with SCS effectiveness was observed in a study with 2% reduction of SCS success with each unit increase of BMI72; and a BMI >36.5 kg/m 2 was associated with less improvement in depression and catastrophizing in patients on SCS therapy 73…”
Section: Committee Statements and Recommendationsmentioning
confidence: 98%